A Comparison of Structuralism and Generative Grammar in Arabic Linguistics - Anisa Tufahati; Ahmad Afif Al-Mumtaz; Ronaa Fitri Butsainah; Fachrul Ghazi (Edumaniora : Jurnal Pendidikan dan Humaniora, 2026)
Linguistic studies have yielded a range of divergent approaches to understanding language structure and usage; perhaps the most prominent and widespread of these are the structuralist and generative approaches. This study aims to compare the two approaches within the context of Arabic linguistic studies by analyzing recent literature and presenting concrete practical examples in the field of education. The goal is to identify the distinctive features of each approach, highlight their contributions to understanding the Arabic language, and identify the challenges they face. The findings indicate that the structuralist and generative approaches offer two distinct yet complementary perspectives in the study of Arabic; the structuralist approach builds a solid understanding of the language’s basic structure, while the generative approach provides a more dynamic perspective for understanding the language’s potential and the scope of its usage. Both contribute to the advancement of linguistic studies and a deeper understanding of the Arabic language.